STRATEGI PENCEGAHAN KORUPSI UNTUK MENURUNKAN TINGKAT KORUPSI DI DAERAH - Bustami Abdul Rajak; Irfan Zamzam; Zulkifli Abu (Nusantara Hasana Journal, 2026)
Corruption At The Local Government Level Remains A Major Challenge That Affects The Quality Of Public Services And The Effectiveness Of Development. This Study Aims To Assess The Effectiveness Of Corruption Prevention Strategies Implemented Through The Monitoring Center For Prevention (MCP) Program And The Integrity Assessment Survey (Survei Penilaian Integritas/SPI) In Tidore Islands City. The Research Employs A Descriptive Qualitative Approach, With Data Collected Through In-Depth Interviews, Observations, And Documentation From Key Informants, Including Local Government Officials, Inspectorate Auditors, And Community Representatives. The Results Indicate That The Implementation Of MCP And SPI Contributes To Strengthening A Culture Of Integrity, Transparency, And Accountability Within The Bureaucracy, As Reflected In The Increase Of The SPI Score From 68.44 To 73.24. However, The Effectiveness Of Corruption Prevention Efforts Still Faces Obstacles, Particularly Related To Limited Human Resources And Inconsistencies In Internal Supervision. This Study Concludes That Strengthening Internal Oversight Functions And Increasing Community Participation Are Crucial Aspects To Ensure The Sustainability Of Corruption Prevention Strategies At The Local Government Level.